Experimental and Modeling Study of Wall Film Effect on Combustion Characteristics of Premixed Flame in a Constant Volume Combustion Bomb - Bai, Shijie; Zhang, Hongsheng; Li, Chang; Wu, Chaohui; Liang, Xingyu; Wang, Kun (Frontiers in Mechanical Engineering, 2022)
The primary objective of the present study was to investigate the impact of wall film on the combustion characteristics of premixed flames in internal combustion engines through the joint experimental and numerical techniques. The interaction between the premixed methane-air flame and n-dodecane film attached to the wall of a constant volume combustion bomb was experimentally examined. The flame propagation processes, as well as pressure evolution were quantitatively characterized. Then, computational fluid dynamic (CFD) simulation was performed incorporating the combustion chemistry model. To enable efficient simulation of the chemically reacting flow in engine chambers, a simplified modeling approach based on a two-step reaction scheme was developed. A compact reaction model for the selected model fuel n-dodecane was constructed and reduced to include 35 chemical species and 180 reactions. The flame propagation process of the premixed flame and its interaction with dry and wet walls was studied. The results showed that the propagation of the premixed flame could be divided into four stages, and the existence of the slit structure increased the instability of the flame structure in the near-wall region. The wall film tended to promote emissions, producing more unburned hydrocarbons, soot precursors and aldehydes.